2016
DOI: 10.15244/pjoes/63782
|View full text |Cite
|
Sign up to set email alerts
|

Regional Frequency Analysis of Annual Peak Flows in Pakistan Using Linear Combination of Order Statistics

Abstract: For this paper we conducted a regional analysis (RA) of annual peak flows using linear combination of order statistics, i.e., linear-moments (LM) and trimmed linear moments (TLM). Design flood estimates are calculated and compared at different return periods, which are useful for water resources management, including hydrological structures and basin management. The main objective of our study was to compare regional design flood estimates for untrimmed and trimmed samples. LM is the special case of TLM, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…For all six distributions, the Z statistics for flood volumes showed that the distributions satisfied the test criteria |Z| < 1.96, N (1.54), LN (0.12), G (1.23), GP (0.33), PIII (0.58) and LPIII (1.52). In this case, when all distributions satisfy the goodness-of-fit test, the distribution closest to zero will be considered as the best fit [41]. As presented, the LN distribution has the value closest to zero, so it can be selected as the appropriate distribution for the flood volumes.…”
Section: Resultsmentioning
confidence: 99%
“…For all six distributions, the Z statistics for flood volumes showed that the distributions satisfied the test criteria |Z| < 1.96, N (1.54), LN (0.12), G (1.23), GP (0.33), PIII (0.58) and LPIII (1.52). In this case, when all distributions satisfy the goodness-of-fit test, the distribution closest to zero will be considered as the best fit [41]. As presented, the LN distribution has the value closest to zero, so it can be selected as the appropriate distribution for the flood volumes.…”
Section: Resultsmentioning
confidence: 99%
“…As described by [ 4 ], extensive literature for FFA is available, not only for the detailed description of PDFs, but also for parameter estimation. The commonly used PDFs for modeling of the APFDs include: generalized extreme value (GEV), generalized logistic (GLO), generalized Pareto (GPA), Pearson type 3 (P3), log Pearson type 3 (LP3), Weibull (WEI), extreme value type 1, extreme value type 2, normal, log normal, gamma, and exponential [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang found that LH-moments produce consistent quantile estimates for large return periods, since LH-moments provide greater weight to the larger values in the APFD series and hence better fits to the upper tail of PDFs. This characteristic is even more relevant when sample sizes are small, which is a common reality of streamflow monitoring in developing countries, including Pakistan [ 8 , 9 , 12 , 13 , 14 ]. Various studies have been conducted on LH-moments in different regions of the world [ 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…RFA has also been applied in a few of the published studies in Pakistan. These include: for rainfall (Ahmad et al, 2013; Ahmad et al, 2016a; Ahmad et al, 2017a; Hussain et al, 2017; Khan et al, 2017; Shahzadi et al, 2013), for floods (Ahmad et al, 2016b; Ahmad et al, 2017b; Batool, 2017; Hussain, 2011; Hussain, 2017; Hussain & Pasha, 2009), for wind (Fawad et al, 2018; Fawad et al, 2019). Highlights of some published literature concerning flood frequency analysis in Pakistan are provided in the following section:…”
Section: Introductionmentioning
confidence: 99%